Improvement the Efficiency CIGS Thin Film Solar Cells by Changing the Thickness Layers (International Journal of Engineering and Computer Science, 2017)
In this study the function of solar cells with the structure of CuIn1-xGaxSe2is examined. CIGS solar cell consists of layers of ZnO (Layer TCO), Cd_S (buffer layer), CIGS (absorbent layer), and Layer MO (substrate), which Cd_S and CIGS layers form a PN Junction. Later using SILVACO software CIGS solar cell is simulated. Then, CIGS solar cell is simulated using SILVACO software, Firstly the thickness of the adsorbent layer is changed. Later thickness of the absorbent layer becomes fixed and the thickness of the Cd_S and ZnO layers are changed respectively and its effect on cell function is discussed and examined. Important parameters of a solar cell that will be discussed here, include open circuit voltage (VOC), short circuit current (ISC), maximum power (Pmax), filling factor (FF) and efficiency (η). After conducted simulations, it was that increasing or decreasing the thickness layers has impact on solar cells function.